The Norm Establishment in WhatsApp Group Conversations - Norwanto Norwanto; Faizal Risdianto (Journal of Language and Literature, 2022)
This linguistics study aims to observe the development of norms in WhatsApp Groups (WAGs). Over the years, linguists have devoted their time to theorizing norms of im/politeness evaluations and linguistic interactions in computer-mediated communication (CMC). However, the norms of virtual interactions have not gained adequate attention. This study systematically documented and examined the conversations of 539 members of three WAGs to describe the norms of virtual group communication. The data obtained were enhanced through anecdotal evidence of the experiences acquired in joining other WAGs. The data indicated four sources of WAGs norms: the aims of creating the group, framing unmarked behaviors, and framing positive or negative evaluations of members' utterances or actions. The members' alignments toward non-virtual individual and social norms also significantly affect their negotiating WAG norms. In the stages of the norming process, WAGs tend to experience conflicts due to interpersonal differences. These disputes are likely to disrupt the group's performance or predispose some members. Theoretically, group development is comprised of formation, conflicts, norming, and performance. Depending on the homogeneity or heterogeneity of the member's background, WAGs do not necessarily experience conflicts in the norming process. However, some of them tend to leap the stages from formation to performance.